2022
DOI: 10.1101/2022.09.05.506655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate flux predictions using tissue-specific gene expression in plant metabolic modeling

Abstract: Motivation: The accurate prediction of complex phenotypes such as metabolic fluxes in living systems is a grand challenge for systems biology and central to efficiently identifying biotechnological interventions that can address pressing industrial needs. The application of gene expression data to improve the accuracy of metabolic flux predictions using mechanistic modeling methods such as Flux Balance Analysis (FBA) has not been previously demonstrated in multi-tissue systems, despite their biotechnological i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These findings could indicate that for these reactions, the fluxes are controlled at the gene expression level [53] . However, other works found that a combination of both omics yields slightly better results [54] , while others point to higher predictive power from proteomics data [55] , [56] . In essence, it seems that the two omics contain relevant information for metabolic modeling and it would probably be best to use a combination of both in order to maximize the amount of available information.…”
Section: Discussionmentioning
confidence: 95%
“…These findings could indicate that for these reactions, the fluxes are controlled at the gene expression level [53] . However, other works found that a combination of both omics yields slightly better results [54] , while others point to higher predictive power from proteomics data [55] , [56] . In essence, it seems that the two omics contain relevant information for metabolic modeling and it would probably be best to use a combination of both in order to maximize the amount of available information.…”
Section: Discussionmentioning
confidence: 95%
“…In favorable cases, individual internal fluxes can be quantitatively estimated in vivo using independent methods and compared directly to ones from a predicted flux map to provide a powerful form of validation. For example, in a study from our group 74 the ratio of the cyclic electron flow (CEF) to linear electron flow (LEF) fluxes in photosynthesis predicted by FBA was evaluated against CEF/LEF ratios from fluorescence measurements for validation purposes. Though less specific, the sum of FBA‐predicted values for fluxes that produce and/or consume a product (such as CO 2 ) can also be compared to experimental measurements.…”
Section: Validation Techniques In Fba and 13c‐mfamentioning
confidence: 99%
“…Moreover, with appropriate experimental constraints the approach can make accurate predictions about the metabolic phenotype (Cheung et al., 2013). The predictive accuracy of the models can be further refined by incorporating ‘omic’ data into the model optimisation process (Kaste & Shachar‐Hill, 2023; Robaina‐Estévez & Nikoloski, 2017; Scheunemann et al., 2018).…”
Section: Introductionmentioning
confidence: 99%